Improved Controller for Interlinking Converter in Hybrid AC/DC Microgrids - Xuan Hoa Thi Pham; Hien-Thanh Le; Hai Van Tran (Journal of Technical Education Science, 2024)
The AC/DC hybrid microgrids are a feasible solution to provide both AC and DC power to electrical equipment. However, the control problem to maintain voltage and frequency stability in AC/DC hybrid microgrids is essential. This paper proposes a control method for the converter to maintain voltage and frequency stability for AC/DC hybrid microgrids. The power converter will operate bidirectionally to transfer power back and forth between AC and DC subgrids in the AC/DC hybrid microgrid operating in standalone mode. The proposed control method not only controls the bidirectional power flow between AC and DC subgrids to stabilize voltage and frequency as well as balance active power and reactive power. In addition, the proposed method can restore voltage and frequency for the microgrid in the event of sudden load surges or power failures in AC and DC subgrids. This method is established based on the relationship between active power and frequency, because active power is present in both AC and DC subgrids, while frequency is only present in AC subgrid. However, in AC subgrid, frequency depends on active power, while in DC subgrid, DC bus voltage depends on active power. Therefore, the proposed method is designed based on adaptive frequency shifting to adjust the power flow exchange between the two subgrids in order to maintain the stability of the frequency and voltage of the buses. The suitability and feasibility of the method are demonstrated by simulating the AC/DC hybrid microgrid using Matlab/simulink software.